No news is good news? The declining information value of broadcast news in America - Johann D. Gaebler; Sean J. Westwood; Shanto Iyengar; Sharad Goel (PLoS ONE, 2025)
Despite the rise of digital media, Americans are five times more likely to consume news via television than through online platforms. However, due in large part to technical hurdles, it remains unclear what content appears on broadcast news and how the mixture of content has changed over time. We consider these questions by applying a novel LLM-based approach to an understudied corpus of expert-generated summaries of virtually all news segments aired on the “big three” broadcast networks—ABC, CBS, and NBC—between 1969 and 2024. Results based on nearly one million news segments show that “information density”—the amount of time dedicated to political issues—has declined substantially over the last 50 years. Today, broadcast news spends roughly twice as much time on commercials and “soft” news and half as much on issue-based political coverage compared to a few decades ago. Since the early 1990s, the news has also shifted inward, focusing more on domestic stories and less on international affairs. These changes suggest a transformation in the informative role of broadcast news, raising questions about its impact on voter knowledge and political engagement.